Efficacy and safety of red onion use in reducing fever in children - Anjeli, A Maya Rupa; Fatmawati, Lilis; Haritami, Sheilla Aziza (Jurnal Keperawatan, 2024)
Introduction:  Fever in children often causes concern for parents as it is the body's response to infection. Red onion, which possesses antimicrobial and anti-inflammatory properties, has garnered attention as an alternative therapy for managing fever. Objectives:  This study aims to evaluate the effect of red onion administration in reducing fever in children, as well as to ensure its efficacy and safety. Methods:  A controlled randomized clinical trial design was employed, involving children with mild to moderate fever. The treatment group received red onion, while the control group received a placebo. Body temperature measurements and fever symptoms were periodically assessed. Results:  The study findings indicate that red onion administration significantly reduces body temperature and accelerates the recovery of fever symptoms in children, without significant adverse effects associated with its use. Conclusions:  Red onion administration in children proves to be effective in safely reducing fever. These findings provide a strong basis for considering the use of red onion as an effective adjunct therapy in managing fever in children. Further research is needed to validate these findings and optimize the use of red onion in pediatric treatment.